INTELLECTUAL PROPERTY PROTECTION OF SHARED CULTURAL HERITAGE THROUGH TRADITIONAL CULTURAL EXPRESSIONS (TCES) IN INDIA: MISSING LEGISLATIVE FRAMEWORK? - Chakraborty, Amlan; Chatterjee, Debalina (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The discussion also occupies prominence in contemporary times with increased emphasis on rights of indigenous peoples occupying the centre-stage at International treaties at global forums such as the Indigenous and Tribal Peoples Convention (1989) (the fore-runner of the subsequent UN declaration of 2007 on indigenous peoples) , Universal Declaration of Human Rights (UDHR) , UN Declaration of the Rights of Indigenous Peoples (2007) . India has ratified the latter two instruments and remains duty-bound to fulfil its obligations there- under. The experiences of absence of legislation and its potential implication in Indian scenario along with policy prescriptions were yet to be documented in any scholarly writings and this paper intends to fill this gap. The general public as well as academic discourse in India pertaining to traditional cultural expressions/folk-lore in this aspect has been wholly muted, if not absent.